1984
DOI: 10.2135/cropsci1984.0011183x002400030022x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Leaf Senescence in Soybean1

Abstract: Leaves of commercial soybeans [Glycine max (L.) Merr.] typically senesce and abscise during seed development, but certain genetic lines produce mature seeds and show a delayed leaf senescence (DLS) phenotype in which leaves remain green until killed by frost. Field studies with such DLS lines provide information on the physiological and agronomic traits associated with such plants. Acetylene reduction and carbon exchange rates of DLS plants declined greatly after seeds matured, but positive values were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Soybean has a number of genotypes that offer variable source and sink qualities. These include some that contain genes promoting or delaying leaf senescence expressed differentially as a function of environmental conditions Phillips et al 1984); male-sterile plants with reduced pod set and delayed senescence (Huber et al, 1983); plants with several genes that affect chlorophyll loss or photosynthesis rate, altering, but not preventing, the senescence program (Nooden and Guiamet 1989;Guiamet et al 1990); and cultivars that respond differently to depodding (Crafts-Brandner and Egli 1987). Sorghum also has a non-senescent phenotype (McBee et al 1983), whereas there are mutants of Phaseolus vulgaris and Festuca pratensis that senescence normally, but have no chlorophyll breakdown (Ronning et al 1991; Thomas and Stoddart.…”
Section: Discussionmentioning
confidence: 99%
“…Soybean has a number of genotypes that offer variable source and sink qualities. These include some that contain genes promoting or delaying leaf senescence expressed differentially as a function of environmental conditions Phillips et al 1984); male-sterile plants with reduced pod set and delayed senescence (Huber et al, 1983); plants with several genes that affect chlorophyll loss or photosynthesis rate, altering, but not preventing, the senescence program (Nooden and Guiamet 1989;Guiamet et al 1990); and cultivars that respond differently to depodding (Crafts-Brandner and Egli 1987). Sorghum also has a non-senescent phenotype (McBee et al 1983), whereas there are mutants of Phaseolus vulgaris and Festuca pratensis that senescence normally, but have no chlorophyll breakdown (Ronning et al 1991; Thomas and Stoddart.…”
Section: Discussionmentioning
confidence: 99%
“…The delayed senescence observed in stay-green genotypes was found to be positively correlated to higher grain yields in sorghum (Rosenow et al, 1983;Phillips et al, 1984;Vietor et al, 1989 andEvangelista &Tangonan, 1990) and maize Silva et al 57 (Duvick, 1984;Russel, 1986;Ceppi et al, 1987). Furthermore it was observed that it provided a resistance to lodging in stay-green sorghum genotypes (Woodfin et al, 1981 andDuncan et.…”
Section: Introductionmentioning
confidence: 96%
“…However, such leaf nutrient depletion could limit the late-season canopy photosynthesis in leguminous crops, indicating that delaying leaf senescence in order to extend the seed-filling period would be a strategy for increasing grain yield (Grabau et al, 1986;Lynch & Rodriguez, 1994). Nevertheless, soybean progeny lines showed an inverse relationship between grain yield and delayed leaf senescence, suggesting that maximum yields can only be achieved in plants whose leaves senesce during pod-filling (Phillips et al, 1984). Therefore, crop improvement should balance the extension of the mature phase of canopy as a carbon source and the rapid recovery of mineral nutrients during leaf senescence (Thomas & Stoddart, 1980).…”
Section: Introductionmentioning
confidence: 99%